Environmental Education Research - Environmental Education Research (Taylor & Francis, 2026)
The mission of Environmental Education Research is to advance research-based and scholarly understandings of environmental and sustainability education. The journal achieves this by publishing peer reviewed research and scholarship on all aspects of environmental education, sourced from around the world and diverse schools of thought and practice in inquiry. The editorial board welcomes submission of original, high quality and innovative papers derived from empirical, philosophical, practice-or policy-related investigations of environmental and sustainability education. The journal’s primary audiences are those working in or with the broad fields of education and educational research, and environmental studies, and relevant interdisciplinary or subdisciplinary aspects.
FI 1.03
Q1
Keywords: Education; Ciencia ambiental; Educación; Acuerdos transformativos; Transformative agreements; Estudios ambientales; Sostenibilidad; Educación ambiental